From traditional channels of service delivery to e-government: Lessons for Zimbabwe - Chilunjika, Alouis (Universitas PGRI Madiun, 2024)
Information and communication technology (ICT) is perceived as a powerful tool for improving the quality and efficiency of government services. The Zimbabwean government has also recognized the importance of the digital revolution for service delivery and has already taken significant steps towards capitalising on the potential benefits that technology brings. However, progress for Zimbabwe has been slow. This study being qualitative in its approach explores the conceptualisation of e-government and the service delivery models by drawing experiences and best practices from other countries. The study relied on the extensive review of purposively selected written documents which are then analysed using thematic and content analysis techniques. Evidence from the selected countries reveals that government commitment towards e-government initiatives is a prerequisite for sustainable service delivery. The study highlighted that Zimbabwe can draw lessons in areas of political will and good leadership, resource commitment, data privacy and security, interoperability, accessibility among others.